In Defense of Wyam : Native-White Alliances and the Struggle for Celilo Village - Barber, Katrine (Book collections on Project MUSE.)
When the US Army Corps of Engineers began planning construction of The Dalles Dam at Celilo Village in the mid-twentieth century, it was clear that this traditional fishing, commerce, and social site of immense importance to Native tribes would be changed forever. Controversy surrounded the project, with local Native communities anticipating the devastation of their way of life and white settler-descended advocates of the dam envisioning a future of thriving infrastructure and industry. In In Defense of Wyam, having secured access to hundreds of previously unknown and unexamined letters, Katrine Barber revisits the subject of Death of Celilo Falls, her first book. She presents a remarkable alliance across the opposed Native and settler-descended groups, chronicling how the lives of two women leaders converged in a shared struggle to protect the Indian homes of Celilo Village. Flora Thompson, member of the Warm Springs Tribe and wife of the Wyam chief, and Martha McKeown, daughter of an affluent white farming family, became lifelong allies as they worked together to protect Oregon's oldest continuously inhabited site. As a Native woman, Flora wielded significant power within her community yet outside of it was dismissed for her race and her gender. Martha, although privileged due to her settler origins, turned to women's clubs to expand her political authority beyond the conventional domestic sphere. Flora's and Martha's coordinated efforts offer readers meaningful insight into a time and place where the rhetoric of Native sovereignty, the aims of environmental movements in the American West, and women's political strategies intersected.